If it's not what You are looking for type in the equation solver your own equation and let us solve it.
65m-2(m-5)=17
We simplify the equation to the form, which is simple to understand
65m-2(m-5)=17
Reorder the terms in parentheses
65m+(-2m+10)=17
Remove unnecessary parentheses
+65m-2m+10=+17
We move all terms containing m to the left and all other terms to the right.
+65m-2m=+17-10
We simplify left and right side of the equation.
+63m=+7
We divide both sides of the equation by 63 to get m.
m=0.111111111111
| 8x-(7x+3)=8x-24 | | 5(x-1)=3x-15 | | -6(3p+3)-18=5(4p+8) | | 1/6y=5/33 | | 18x+25=6(3x-4) | | 2=p/2-1 | | t+2t=12 | | x=6+0.125y | | 20*x+83=223 | | 2(x+6)=8x+-6x+4 | | 2x+7y=475x+4y=50Findxy | | 5m+25=9m-3 | | 5x+3=2(x+3)+3x-3 | | 2+1/3t=1+1,3 | | 5(y-1)=3x-15 | | 8x-(4x+3)=13 | | 3/30=n/80 | | 5x+3=2(x+3)+3x | | 17=w/5-8 | | w/2-(-8)=10 | | x-1/6+1/3 | | 7x+11+10=0 | | 8x+3=-19 | | 25=2(x-3) | | 6(7-2x)=12+3(x-5) | | 1=b/4-8 | | d+d+3=17 | | 2m+5=5m-4 | | 3s+5s=1-8s | | 9x-3+2x-3=9x | | -13=t/2-16 | | 7n+5n=36 |